2000
DOI: 10.1016/s0006-3495(00)76381-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ca2+ Sparks by Ruthenium Red in Permeabilized Rat Ventricular Myocytes

Abstract: We have compared the effects of the sarcoplasmic reticulum (SR) Ca(2+) release inhibitor, ruthenium red (RR), on single ryanodine receptor (RyR) channels in lipid bilayers, and on Ca(2+) sparks in permeabilized rat ventricular myocytes. Ruthenium red at 5 microM inhibited the open probability (P(o)) of RyRs approximately 20-50-fold, without significantly affecting the conductance or mean open time of the channel. At the same concentration, RR inhibited the frequency of Ca(2+) sparks in permeabilized myocytes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 49 publications
8
74
2
Order By: Relevance
“…s Ahluwalia et al (2002). t Ruthenium red has been reported to interact with TRPV5 (Nilius et al, 2001), TRPV6 (Nilius et al, 2001), voltage-gated calcium channel (Cibulsky and Sather, 1999), and ryanodine receptor (Lukyanenko et al, 2000).…”
Section: Trpv1 In Body Temperature Regulationmentioning
confidence: 99%
“…s Ahluwalia et al (2002). t Ruthenium red has been reported to interact with TRPV5 (Nilius et al, 2001), TRPV6 (Nilius et al, 2001), voltage-gated calcium channel (Cibulsky and Sather, 1999), and ryanodine receptor (Lukyanenko et al, 2000).…”
Section: Trpv1 In Body Temperature Regulationmentioning
confidence: 99%
“…Ca 2ϩ sparks were quantified by using a detection computer algorithm, and their statistics were corrected for missed events and amplitude distortions introduced by instrumental noise. 16,17 Data were expressed as meansϮSE. Comparisons were performed by using the paired t-test, and significance was defined at PϽ0.05.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…objective. 16 Fluo-3 was excited by light at 488 nm (25-mW argon laser, intensity attenuated to 0.3%), and the fluorescence was acquired at wavelengths of Ͼ515 nm in the line scan mode at rate of 6.0 ms per scan. Ca 2ϩ sparks were quantified by using a detection computer algorithm, and their statistics were corrected for missed events and amplitude distortions introduced by instrumental noise.…”
mentioning
confidence: 99%
“…The filling state of the SR must reflect the balance between the rate of loss through leak pathways and the rate of Ca 2ϩ uptake via Ca 2ϩ -ATPase. Recent studies in cardiac myocytes have suggested that Ca 2ϩ leak is more important in setting the SR load than the thermodynamic limits of the Ca 2ϩ pump (9,(16)(17)(18). It has also been postulated that the resting SR load in smooth muscle is also limited by Ca 2ϩ leak (33).…”
mentioning
confidence: 99%